Experiment and analysis of intake pipe for single cylinder engine - Mohd Redzuan, Hasan (2013)
Internal combustion engine is one of beautiful engineering knowledge in engineering scope. Internal combustion consists of two type categories which are Spark Ignition (SI) and Compression Ignition (CI). Based on internal combustion engine, a lot of research can be done to improve the performance of engine, fuel consumption, and emission. One of the researches is Experiment and Analysis of Intake Design for Single Cylinder Engine. The main objective is to study the variable design length to increase the performance of the engine. The second is to obtain high power and torque at low speed of engine (rpm) based on the change of intake parameter. The experiment is handle by utilize the Eddy Current Dynamometer 15kW. There are two difference length of intake pipeline which is 52mm and 73mm. the length that change are from 90 degree angle until joining of intake pipe. Before undergo the experiment, test rig of the engine need to fabricate because the engine that use is difference from previous experiment of dynamometer. To fabricate the test rig, four elements involve which are sketching, designing, analysis, and fabrication. These experiments consist of three different result which is baseline graph, length of intake 52mm and length of intake 73mm. The graphs are plot for power and torque graph versus speed of engine. When there are changes of the length of the intake pipe, the torque graph will be change according to the difference length. The increasing of the length, the result of torque and power graph will be more improve. But there are limit to make sure the intake pipe length not give bad impact to the engine. The result concluded that, the better length of intake pipe is the longer one which is 73mm and this result can be applied to student formula race